The Poetics of Robert Blair - Mrvík, Antonín (Univerzita Pardubice, 2010)
The work describes the life, work and poetics of Robert Blair. It attempts to discuss the history of composition of the poet´s work of renown, The Grave, the literary influences upon the poem, and the resulting effect the piece was to have upon its readers.
Poetika Roberta Blaira
Keywords: poezie osmnáctého století; literární vlivy; religiozita; hřbitovní škola; Robert Blair; eighteenth-century poetry; literary influence; religiousness; Graveyard School; William Shakespeare